What strange creatures : a novel - Arsenault, Emily (William Morrow, 2014)
"After her brother is arrested for murder, Theresa's quiet life is turned upside down as she immerses herself in a world of political and legal scandal, white-collar crimes and controversial convictions in order to prove his innocence in the next gripping literary mystery by critically acclaimed author Emily Arsenault"--